2007
DOI: 10.1007/s10995-007-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Linguistic and Cultural Validity of the Spanish Language Version of the Children with Special Health Care Needs Screener

Abstract: When parents were interviewed in English, 11.7% of Hispanic children were identified as CSHCN. When parents were interviewed in Spanish, 5.1% of Hispanic children were identified as CSHCN. Lower prevalence of the need for or use of prescription medications for chronic conditions made the largest contribution to the observed difference in CSHCN prevalence. Cognitive interviews with parents did not identify any linguistic or cultural deficiencies in the Spanish translation of the CSHCN Screener. Parents did expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
0
24
1
1
Order By: Relevance
“…[19][20][21][22] An earlier study identified reluctance on the part of Hispanic parents who have limited English proficiency to disclose details about their children's health to anonymous telephone interviewers, 4 yet we found that the parents of Hispanic CSHCN living in Spanish-language households were as likely as parents of non-Hispanic white CSHCN to report the functional difficulties of their children.…”
contrasting
confidence: 54%
See 3 more Smart Citations
“…[19][20][21][22] An earlier study identified reluctance on the part of Hispanic parents who have limited English proficiency to disclose details about their children's health to anonymous telephone interviewers, 4 yet we found that the parents of Hispanic CSHCN living in Spanish-language households were as likely as parents of non-Hispanic white CSHCN to report the functional difficulties of their children.…”
contrasting
confidence: 54%
“…12 Results of cognitive testing, however, indicate that the Spanish translations of the questions are well understood both culturally and linguistically by parents whose primary spoken language is Spanish. 4 Psychometric assessment of the screening instrument also did not reveal any measurement bias when comparing Hispanic children from Spanish-speaking households to other groups of children. 13 To better understand the nature of this disparity in CSHCN prevalence, we used data from the 2005-2006 NS-CSHCN to examine the health care needs of Hispanic children and focused on those who live in households in which Spanish is the primary language spoken.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Na versão em espanhol foi verificada a mesma dificuldade 13 . Ademais, aqueles em atendimento no ambulatório avaliaram a utilização do serviço médico como rotina e não como um follow-up.…”
Section: Resultsunclassified